METHODS OF TEACHING SOCIAL JUSTICE AND EQUALITY TO STUDENTS - Ikromova Sitora Akbarovna (Economics, management, and digital innovation in education: contemporary trends and approaches, 2025)
This in the article general middle education in institutions to students social justice and equality concepts of formation effective methods illuminated . Social justice and equality society development important from factors one as looking at this values young generation to the mind of absorption pedagogical basics open given . In the article modern approaches , interactive methods and education environment socio-psychological factors analysis will be done .